Do short-term laboratory experiments provide valid descriptions of long-term economic interactions? A study of Cournot markets - Hans-Theo Normann; Till Requate; Israel Waichman (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2013)
One key problem regarding the external validity of laboratory experiments is their duration: while economic interactions out in the field are often lengthy processes, typical lab experiments only last for an hour or two. To address this problem for the case of both symmetric and asymmetric Cournot duopoly, we conduct internet treatments lasting more than a month. Subjects make the same number of decisions as in the short-term counterparts, but they decide once a day. We compare these treatments to corresponding standard laboratory treatments and also to short-term internet treatments lasting one hour. We do not observe differences in behavior between the short- and long-term in the symmetric treatments, and only a small difference in the asymmetric treatments. We overall conclude that behavior is not considerably different between the short- and long-term.
Keywords: L13; C93; C72; D43; D21; 330; internet experiment; Cournot oligopoly; long-term interactions; methodology; internet vs. laboratory experiment